2015
DOI: 10.1515/helmin-2015-0055
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism and pathogenicity of curly-leaf parsley with the root-knot nematode Meloidogyne javanica in Southern Italy

Abstract: SummarySevere infections of parsley plants and soil infestations with Meloidogyne javanica during an autumn surveys for the pathogenic root-knot nematode infestations were found in Monopoli at Bari province in Southern Italy. This unusual severe infection of parsley, considered a winter crop, was possibly instigated by a very warm autumn from the previous year. Nematodes were extracted from soil samples according to the Coolen's method. Morphological analysis (based on stylet length, tail length and shape, adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The damage caused by root-knot nematodes on the leaves of the consumed part of parsley is economically important and it is an undesirable situation for the growers. In the previous studies conducted around the world, it has been reported that parsley is a suitable host for Root-knot nematodes (M. arenaria, M. enterolobii, M. floridensis, M. incognita, M. hapla, M. hispanica and M. javanica) (Doucet & Pinochet 1992;Sikora & Fernández, 2005;Mennan et al, 2011;Quénéhervé et al, 2011;Maleita et al, 2012;Sasanelli et al, 2015). However, this is the first report of a parsley plant as a host for M. hapla species in Turkey.…”
Section: Meloidoyne Hapla Petroselinum Crispum Teşhis çAnakkalementioning
confidence: 81%
“…The damage caused by root-knot nematodes on the leaves of the consumed part of parsley is economically important and it is an undesirable situation for the growers. In the previous studies conducted around the world, it has been reported that parsley is a suitable host for Root-knot nematodes (M. arenaria, M. enterolobii, M. floridensis, M. incognita, M. hapla, M. hispanica and M. javanica) (Doucet & Pinochet 1992;Sikora & Fernández, 2005;Mennan et al, 2011;Quénéhervé et al, 2011;Maleita et al, 2012;Sasanelli et al, 2015). However, this is the first report of a parsley plant as a host for M. hapla species in Turkey.…”
Section: Meloidoyne Hapla Petroselinum Crispum Teşhis çAnakkalementioning
confidence: 81%
“…The warm climatic conditions seem to be favorable for Meloidogyne infection on leaf parsley since most reports on Meloidogyne reducing leaf parsley growth are from the warmer regions. For example, severe losses of leaf parsley due to Meloidogyne have been reported for M. incognita and M. enterolobii in Venezuela [14,15], M. arenaria in Argentina [23] and Turkey [17], and M. javanica in South Italy [16]. Nonetheless, temperate Meloidogyne species can also reduce leaf parsley growth under favorable conditions, such as shown for M. hapla infecting leaf parsley roots during the winter season in the Marmara region, Turkey [24].…”
Section: Effect Of Meloidogyne Hapla M Chitwoodi M Fallax and M Incog...mentioning
confidence: 99%
“…As a result, Meloidogyne infection may lead to stunted plant growth and reduced yield. While there are several reports of Meloidogyne species affecting leaf parsley in warmer regions [14][15][16][17], little is known about Meloidogyne damage on leaf parsley in temperate regions. In this study, we aimed to investigate the host status and plant growth response of European flat-leaf and curly-leaf parsley cultivars towards Meloidogyne species from temperate regions, i.e., M. hapla, M. chitwoodi, and M. fallax, as well as M. incognita, one of the most common pathogens in subtropical and tropical regions.…”
Section: Introductionmentioning
confidence: 99%
“…The main nematode species associated with curly leaf parsley are: Ditylenchus dipsaci (Kuhn) Filipjev, Belonolaimus gracilis Steiner, Dolichodorus M. enterolobii Uang y Eisenback, M. floridensis Chitwood, Hannon y Esser, M. incognita (Kofoid y White) Chitwood, M. hapla Chitwood, M. hispanica Hirschmann, and M. javanica (Treub) Chitwood (Mennan et al, 2011;Maleita et al, 2012;Barros et al, 2018;Hallmann y Meressa, 2018). Plants infected by these Meloidogyne species show symptoms related to generalized decay, leaf yellowing, reduced shoot growth, reduction of the root system, and presence of root galls (Mennan et al, 2011;Sangronis et al, 2014;Sasanelli et al, 2015;Hallmann y Meressa, 2018;Ntalli et al, 2019), and M. arenaria has also been reported to cause economic damages in P. crispum 'Bezirci', in Turkey (Mennan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%